Prior consultation as a guarantee of the collective rights of indigenous peoples: A literature review (International Journal of Environmental Sciences, 2025)
This study examines prior consultation as a guarantee of the collective rights of Indigenous peoples. A literature review was conducted, including qualitative, quantitative, mixed-methods, bibliographic, and literature review studies. Thirty scientific articles were selected from the Scopus and SciELO databases, published between 2018 and 2024 in Spanish and English, following strict inclusion and exclusion criteria. After rigorous evaluation, these articles provided robust scientific evidence on the impact and effectiveness of prior consultation in protecting the territorial, cultural, and self-determination rights of Indigenous peoples. The findings reveal that, although there is formal recognition of this right, its implementation faces significant challenges, particularly in contexts of extractive expansion and energy transition. This analysis contributes to a critical understanding of prior consultation as both a tool of resistance and a means of building autonomy in scenarios of intense socio-environmental conflict. It also proposes future research directions focused on strengthening mechanisms for effective participation and informed consent.